Śmierć króla i chustka Teodory - Galant, Arleta (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The author interprets two novels by Zofia Nałkowska — Węzły życia [The Bonds of Life] and Niecierpliwi [The Impatient]. In a hermeneutic-feminist analysis of selected figures and motifs, the article presents new meanings of concepts that are crucial for the understanding of anthropology of corporeality in Nałkowska’s writing project. Among the focal points of the discussion there are the dignity of “lay bodies,” as well as “male” and “female” fantasies of violence.